2015
DOI: 10.1111/bjd.14244
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for presurgical margin assessment by reflectance confocal microscopy of basal cell carcinoma

Abstract: This new procedure helped to improve the identification of proper margins for surgical excision in nonpigmented BCC with clinically and dermoscopically ill-defined margins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 28 publications
(66 reference statements)
0
38
0
3
Order By: Relevance
“…Our result for 4 of 16 BCCs revealed that subclinical extension by HIS is quite similar to RCM in the preoperative in vivo assessment of the margins, as in Venturini et al . 's study, RCM found subclinical extension in 3 of 10 cases compared to the dermatoscopically assessed margins prior to excision. OCT found the subclinical extension of BCC in 11 of 52 cases compared to clinical evaluation by a Mohs surgeon .…”
Section: Discussionmentioning
confidence: 78%
“…Our result for 4 of 16 BCCs revealed that subclinical extension by HIS is quite similar to RCM in the preoperative in vivo assessment of the margins, as in Venturini et al . 's study, RCM found subclinical extension in 3 of 10 cases compared to the dermatoscopically assessed margins prior to excision. OCT found the subclinical extension of BCC in 11 of 52 cases compared to clinical evaluation by a Mohs surgeon .…”
Section: Discussionmentioning
confidence: 78%
“…Regarding BCC margin assessment, Venturini and colleagues 5,6 proposed a new feasible procedure for presurgical evaluation. Briefly, after the application of topical anesthesia, the lesion is analyzed by dermoscopy.…”
Section: In Vivo Applications Of Reflectance Confocal Microscopymentioning
confidence: 99%
“…15 The use of the handheld device makes possible a quick imaging of several lesions in a given patient and thus made possible the concept of one-stop shop treatment for BCC. 20,21 In this procedure, the lesion is first analysed by means of handy dermoscopy. 18,19 Basal cell carcinoma margin assessment Regarding BCC margin assessment, a new feasible procedure for later presurgical in vivo diagnosis of BCC has been identified.…”
Section: Introductionmentioning
confidence: 99%